Dampak Thrifting terhadap Industri Tekstil Indonesia: Perspektif PT. Sritex dan Kebijakan Pemerintah - Siti Afiyah Hardinar Nazhifah; Zakia Zamielna Putri; Shandy Zahra Permadi; Shakila Dian Nova; Alsheira Nasywa; Ahmad Setiawan Nuraya (Journal of Innovative and Creativity, 2025)
The phenomenon of thrifting, or purchasing imported second-hand clothing, is growing in Indonesia and has a significant impact on the national textile industry. This study aims to analyze the impact of the thrifting phenomenon on Indonesia’s textile industry, using a case study of PT Stitex, as well as government policies regulating the trade of imported second-hand clothing. This research employs a mixed-method approach, combining qualitative analysis through non-numeric data analysis and literature studies, along with quantitative analysis using statistical data on the impact of thrifting on the textile industry. The findings indicate that the trade of imported second-hand clothing poses challenges for the local textile industry, particularly in terms of price competition and shifting consumer preferences. PT Sritex has experienced a decline in competitiveness due to the increasing demand for thrifting products. From a regulatory perspective, the government has issued a ban on second-hand clothing imports as a measure to protect the domestic industry. However, the implementation of this policy faces challenges, such as weak enforcement and the continued circulation of illegally imported second-hand clothing. Therefore, more effective strategies from both the government and industry players are needed to enhance the competitiveness of local products and strengthen the enforcement of import regulations on second-hand clothing.